PENDIDIKAN YANG BERKUALITAS PERSPEKTIF HADRATUSYSYAIKH KYAI HASYIM ASY’ARI - Novira Arafah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
This study aims to find how to: (1) The Nature of Education and Quality, (2) Forming Factors of Quality Education Perspective of Hasratusy Shaykh Kyai Hasyim Asy'ari, (3) The Meaning of Quality Education Perspective of Hasratusy Shaikh Kyai Hasyim Asy'ari. The method used is qualitative research and approach library research. The results of research on the Quality of Education Perspective Hadratusysyaikh Kyai Hasyim Asy'ari shows that: quality educational rights are educators (muta’allim) and students (‘alim) who always improve and improve their competence, which is determined by 2 factors , namely: behavior and the flow of knowledge from the teacher's blessing, as well as the meaning of KH.Hasyim Asy'ari's perspective of education is the stage in taking and obtaining knowledge must be with a clear, careful and detailed sanitation and accompanied by a sincere, and pure heart.